Structure elucidation of antiproliferative bisbenzylisoquinoline alkaloids from Anisocycla grandidieri from the Madagascar dry forest1. (10th June 2013) - Liu, Yixi; Harinantenaina, Liva; Brodie, Peggy J.; Slebodnick, Carla; Callmander, Martin W.; Rakotondrajaona, R.; Rakotobe, Etienne; Rasamison, Vincent E.; TenDyke, Karen; Shen, Yongchun; Kingston, David G. I.
Abstract : Antiproliferative bioassay‐guided fractionation of the ethanol extract of the stems of Anisocycla grandidieri led to the isolation of the known alkaloids stebisimine (1), (+)‐1, 2‐dehydrotelobine (2), (+)‐2'‐norcocsuline (3) and puetogaline B (4). Herein, we report the full NMR assignments of all compounds and the X‐ray crystallography of single crystals of compounds 1 and 3. Compounds 2 and 3 showed moderate antiproliferative activity against the A2780 human ovarian cancer cell line with IC50 values of 4.1 ± 0.3 and 2.7 ± 0.3 μM, respectively, and they also displayed selective activity toward the H460 (large cell lung cancer), MCF‐7 (breast ductal carcinoma), and UACC‐257 (melanoma) cell lines. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Antiproliferative bioassay‐guided fractionation of the ethanol extract of the stems of Anisocycla grandidieri led to the isolation of the known alkaloids stebisimine (1), (+)‐1, 2‐dehydrotelobine (2), (+)‐2'‐norcocsuline (3) and puetogaline B (4). Herein, we report the full NMR assignments of all compounds and the X‐ray crystallography of single crystals of compounds 1 and 3. Compounds 2 and 3 showed moderate antiproliferative activity against the A2780 human ovarian cancer cell line with IC50 values of 4.1 ± 0.3 and 2.7 ± 0.3 μM, respectively, and they also displayed selective activity toward the H460 (large cell lung cancer), MCF‐7 (breast ductal carcinoma), and UACC‐257 (melanoma) cell lines .